(untitled) (Journal of actual problems of jurisprudence, 2018)
This article is devoted to criminal offenses in the sphere of economic activity. The author places emphasis that economic crimes are considered as object of criminal law, criminalistics and criminal activity of the Republic of Kazakhstan. In article are considered the general characteristic and concept of economic crimes, and also its signs and types. The criminal legislation of the Republic of Kazakhstan does not perpetuate the notion of criminal offenses in the sphere of economic activity. Author and expressed their views on this issue and give its definition of a criminal offense in the sphere of economic activity. Key words: criminal offenses, crimes, economic crimes, statistics of criminal offenses, criminal code, criminalistics, criminal procedure activity, etc.